2019
DOI: 10.1002/clc.23288
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is reduced prior to ventricular arrhythmias in patients with a wearable cardioverter defibrillator

Abstract: IntroductionThe utility of accelerometer‐based activity data to identify patients at risk of sustained ventricular tachycardia (VT) or ventricular fibrillation (VF) has not previously been investigated. The aim of the current study was to determine whether physical activity is associated with manifesting spontaneous sustained VT/VF requiring emergent defibrillation in patients with an ejection fraction of ≤35%.MethodsPatients consecutively prescribed a wearable cardioverter defibrillator (WCD) from April 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…To further establish the clinical utility of the WCD accelerometer, researchers examined the predictability of VT/VF based on patient activity. Data from 4,057 patients prescribed WCD suggested that patient who achieved less than 3637 steps/day during the first week of their prescription were 4.3 times more likely to experience VT/VF requiring shock 20 . These results are significant, as they represent an important clinical cutoff.…”
Section: Activitymentioning
confidence: 93%
See 2 more Smart Citations
“…To further establish the clinical utility of the WCD accelerometer, researchers examined the predictability of VT/VF based on patient activity. Data from 4,057 patients prescribed WCD suggested that patient who achieved less than 3637 steps/day during the first week of their prescription were 4.3 times more likely to experience VT/VF requiring shock 20 . These results are significant, as they represent an important clinical cutoff.…”
Section: Activitymentioning
confidence: 93%
“…Examination of patient activity via device accelerometer represents another potential data point for risk stratification in patients with WCD (Table 2). 20,21 The WCD accelerometer has established utility as a reliable tool for home-based 6MWT. 22 In the TRENDS study, comparisons of home-based versus clinic-based 6MWT for 197 patients, indicated that patients who were compliant with the frequency of their homebased prescription had no statistically significant difference between the results of home-based versus clinic-based 6MWT.…”
Section: Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…A major component of comprehensive CR is physical activity to improve functional capacity and cardiopulmonary fitness. The 6 min walk test (6MWT) is an effective, reproducible yet simple measure of submaximal cardiopulmonary exercise capacity [9][10][11][12][13]. In addition, the 6MWT has been validated in the setting of CR [14].…”
Section: Introductionmentioning
confidence: 99%
“…10 Conversely, acute increases in physical activity in the setting of overall deconditioning can predispose to a proarrhythmic sympathetic surge. 11 There is ample precedent for the clinical utility of physical activity estimates derived from implantable device accelerometers, and Burch and colleagues 12 have previously demonstrated correlations between low step counts as measured by WCD external accelerometers and incidence of VA. It has been established that physical activity measurements from implanted devices perform well as a surrogate for NYHA functional class and hold predictive value in models estimating risk for VA, SCD, and other adverse cardiac events.…”
mentioning
confidence: 99%